Autophagy and Ubiquitination in Salmonella Infection and the Related Inflammatory Responses - Wang, Lidan; Yan, Jing; Niu, Hua; Huang, Rui; Wu, Shuyan (Frontiers in Cellular and Infection Microbiology, 2018)
Salmonellae are facultative intracellular pathogens that cause globally distributed diseases with massive morbidity and mortality in humans and animals. In the past decades, numerous studies were focused on host defenses to Salmonella infection. Autophagy has been demonstrated to be an important defense mechanism to clear intracellular pathogenic organisms, as well as a regulator of immune responses. The ubiquitin modification also has multiple effects on the host immune system against the bacterial infection. It has been indicated that ubiquitination plays critical roles in recognition and clearance of some invading bacteria by autophagy. Additionally, the ubiquitination of autophagic core proteins in autophagy flux and inflammation-related substance determines the outcomes of infection. However, many intracellular pathogens manipulate the ubiquitination system to counteract the host immunity. Salmonella interferes with host responses via the delivery of approximately 30 effector proteins into the cytosol to promote its replication. Among them, some could link the ubiquitin-proteasome system with autophagy during infection and affect the host inflammatory response. In this review, novel findings on the issue of ubiquitination and autophagy connection as the mechanisms of host defence against Salmonella infection and the subverted processes are introduced.